Health human resources for emergency medicine: a framework for the future. Issue 1 (January 2020) - Sinclair, Douglas; Toth, Peter; Chochinov, Alecs; Foote, John; Johnson, Kirsten; McEwen, Jill; Messenger, David; Morris, Judy; Pageau, Paul; Petrie, David; Snider, Carolyn
ABSTRACT: In June of 2016, the Collaborative Working Group (CWG) on the Future of Emergency Medicine presented its final report at the Canadian Association of Emergency Physicians (CAEP) annual meeting in Quebec City. The CWG report made a number of recommendations concerning physician Human Health Resource (HHR) shortfalls in emergency medicine, specific changes for both the Royal College of Physicians and Surgeons of Canada (FRCPC) and the College of Family Physicians of Canada (CCFP-EM) training programs, HHR needs in rural and remote hospitals, future collaboration of the CCFP-EM and FRCPC programs, and directions for future research. All recommendations were endorsed by CAEP, the Royal College of Physicians and Surgeons of Canada (RCPSC), and the College of Family Physicians of Canada (CFPC). The CWG report was published in CJEM and has served as a basis for ongoing discussion in the emergency medicine community in Canada. The CWG identified an estimated shortfall of 478 emergency physicians in Canada in 2016, rising to 1071 by 2020 and 1518 by 2025 assuming no expansion of EM residency training capacity. In 2017, the CAEP board struck a new committee, The Future of Emergency Medicine in Canada (FEMC), to advocate with appropriate stakeholders to implement the CWG recommendations and to continue with this important work. FEMC led a workshop at CAEP 2018 in Calgary to develop a regional approach to HHR advocacy, recognizing different realities in each province and region. There was wide representation at this workshop and a rich and passionate discussion among those present. This paper represents the output of the workshop and will guide subsequent deliberations by FEMC. FEMC has set the following three goals as we work toward the overarching purpose to improve timely access to high quality emergency care: (1) to define and describe categories of emergency departments (EDs) in Canada, (2) define the full time equivalents required by category of ED in Canada, and (3) recommend the ideal combination of training and certification for emergency physicians in Canada. A fourth goal supports the other three goals: (4) urge further consideration and implementation of the CWG-EM recommendations related to coordination and optimization of the current two training programs. We believe that goals 1 and 2 can largely be accomplished by the CAEP annual meeting in 2020, and goal 3 by the CAEP annual meeting in 2021. Goal 4 is ongoing with both the RCPSC and the CFPC. We urge the EM community across Canada to engage with our committee to support improved access and EM care for all Canadians.